EFFECT OF Mg (II) METAL ION ON ANTIOXIDANT ACTIVITIES OF ETHANOL EXTRACTS OF RAMBUTAN PEEL (Nephelium lappaceum) - Emmi Astuti; Ahyar Ahmad; Seniwati dali (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2018)
Anthocyanin is the one of natural dyes that often used in foodstuffe, because anthocyanin can make a more color like red, blue and purple. Anthocyanin storage can make anthocyanin is damage, because the interaction with tempherature, light, and oxygen show that can given effect about the stability anthocyanin color, and decrease the anthocyanin as an antioxidant. That problem can be solved with copigmentation, that is an anthocyanin reaction with metal ion. In this study can showed that ethanol extract from Rambutan peel and we obtained 23.824 gram with total anthocyanin content of 709.3866 mg/L with antioxidant activity of 0.0046 μg/mL, and then the extract of anthocyanin with metal ion Mg2+ in concentration 50; 100 and 150 ppm had IC50 are 0.0061; 0.0048 and 0.0067 μg/mL. This conclution from the added of metal ion Mg2+ showed that has not show much different antioxidant activity.